Women and Poverty in India: Poverty Alleviation and Empowerment through Cooperatives - Bishnu Mohan Dash; Lokender Prashad; Kislay Kumar Singh; Mitu Dash (Social Work and Society, 2020)
The women's status in the Indian history fluctuated from a position of authority and freedom to that of subservience. The societal norms and beliefs, subjugated status, gendered power dynamics, and unequal hold on properties highlight that women experience poverty differently from men. In India, women are indeed proportionately overrepresented in the informal sectors. This gendered inequality in labour force led to the subjugation of women in all aspects. Additionally, they also bear the burden of unpaid domestic works and are even are denied from some fundamental rights that are enshrined in the constitution of India. In this backdrop, cooperatives are seen as an effective organization for women's empowerment. Cooperatives as democratic organizations has empowered its members to define, decide and direct the affairs of the cooperatives in a participative way for the fulfilment of their common interests. The study has used the data trend analysis and univariate percentage distribution for analysis of data from various secondary sources like census data, reports of National Cooperative Union of India and National Health and Family survey. The findings of the study show that cooperatives in India have played a predominate role in poverty alleviation and women's empowerment in India. However various impediments have constrained the growth of women's cooperative movement in India.